Dry-powder formulations of non-covalent protein complexes with linear or miktoarm copolymers for pulmonary delivery - Nieto-Orellana, Alejandro; Coghlan, David; Rothery, Malcolm; Falcone, Franco H.; Bosquillon, Cynthia; Childerhouse, Nick; Mantovani, Giuseppe; Stolnik, Snow (Elsevier, 2018)
Pulmonary delivery of protein therapeutics has considerable clinical potential for treating both local and systemic diseases. However, poor protein conformational stability, immunogenicity and protein degradation by proteolytic enzymes in the lung are major challenges to overcome for the development of effective therapeutics. To address these, a family of structurally related copolymers comprising polyethylene glycol, mPEG2k, and poly(glutamic acid) with linear A-B (mPEG2k-lin-GA) and miktoarm A-B3 (mPEG2k-mik-(GA)3) macromolecular architectures was investigated as potential protein stabilisers. These copolymers form non-covalent nanocomplexes with a model protein (lysozyme) which can be formulated into dry powders by spray-drying using common aerosol excipients (mannitol, trehalose and leucine). Powder formulations with excellent aerodynamic properties (fine particle fraction of up to 68%) were obtained with particle size (D50) in the 2.5 µm range, low moisture content (<5%), and high glass transitions temperatures, i.e. formulation attributes all suitable for inhalation application. In aqueous medium, dry powders rapidly disintegrated into the original polymer-protein nanocomplexes which provided protection towards proteolytic degradation. Taken together, the present study shows that dry powders based on (mPEG2k-polyGA)-protein nanocomplexes possess potentials as an inhalation delivery system.